Plant-derived Antiviral Compounds as Potential COVID-19 Drug Candidates: In-silico Investigation in Search of SARS-CoV-2 Inhibitors - Kolita, Bhaskor; Borah, Dimplly; Hazarika, Pinaki; Phukan, Ely; Borah, Rashmi Rekha (Trends in Sciences, 2023)
Corona virus disease 2019 (COVID-19) is an infectious disease caused by SARS-CoV-2, a newly discovered pathogenic corona virus that causes respiratory illness in humans and has now become a major challenge for the entire world. Although several vaccines for COVID-19 have been approved to date, lead compounds are still in high demand for the development of more promising or effective drugs and vaccines. According to the literature, antiviral drugs are used to treat COVID-19; thus, the current study is an attempt to screen lead molecules from plant-derived antiviral compounds. In this study, 33 plant-derived compounds with antiviral properties against corona viruses were used as ligand molecules, with Favilavir, Remdesivir, Ivermectin, and Dexamethasone serving as reference drugs. Molecular docking was performed between the selected ligands and the four main drug targets of SARS-CoV-2, Nucleocapsid Protein, Spike Glycoprotein, Proteases 3CLpro, and Helicase, and ADMET properties of screened compounds were observed. Docking results revealed that Reserpine, Tetrandrine, and Xanthoangelol F had a high Moldock score with each target, just like the current COVID-19 medications, Ivermectin and Remdesivir. Docking and ADMET studies indicate that Reserpine, Tetrandrine, and Xanthoangelol F may be potent lead compounds for the treatment of COVID-19 and should be investigated further. HIGHLIGHTS Corona virus disease 2019 (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus that poses a threat to humans Plant-derived drugs have showed significant antiviral activity against SARS-CoV, MERS-CoV29, HCoV-229E, and HCoV-OC43 The current study is an in-silico evaluation of plant-derived SARS-CoV-2 inhibitors. Molecular docking and hydrogen bond interaction studies were performed between the selected plant-derived compounds and vital targets of SARS-CoV-2 to evaluate antiviral efficacy against COVID-19, followed by an ADMET study of the screened ligands This in-silico study determined the antiviral potential of plant-derived compounds against SARS-CoV-2, of which Reserpine, Tetrandrine, and Xanthoangelol F may be potent lead compounds for the treatment of COVID-19 GRAPHICAL ABSTRACT